Perspectives in Company Law and Financial Regulation - Tison, Michel (International Corporate Law and Financial Market Regulation, 2009)
Cover; Half-title; Series-title; Title; Copyright; Contents; List of contributors; Foreword; Part I Perspectives in company law; Part II Perspectives in financial regulation; Part III Miscellaneous; Index